Colitis microscópica: un diagnóstico diferencial a considerar. Presentación de una experiencia local y revisión de la literatura - Figueroa C. , Carolina; Quera P., Rodrigo; Smok S. , Gladys; Galdames I., Kathia; Vallejos, Patricio (Revista Hospital Clínico Universidad de Chile, 2007)
Introduction: microscopic colitis is a cause of chronic diarrhea. The colonoscopy is normal but it has typical histologic findings. The etiology is unknowed but it seems to be an autoimmune factor. There are few case reports in Chile. Aim: To show the clinical characterisitics and evolution of a group of patients with microscopic colitis attended in our hospital. Patients and methods: a retrospective chart review was carried out on 39 cases of microscopic colitis diagnosed in Hospital Clinico de la Universidad de Chile between 1991 and 2005. Results: 68% were women. The mean age of patients was 53 years. Autoimmune disease was diagnosed in 8 patients. The colonoscopy was normal in 65%. The 100% of colagen colitis was women. The patients were treated symptomatically in 51%, antibiotics 18%, esteroids 8%, azulfidine 5%, loperamide 8%. 59% was controled during a year after the diagnosis and 100% was asymptomatic. Conclusions: the results are similar than literature. We need prospective investigation to have strong evidencein the association of microscopic colitis and autoimmune diseases.